2018
DOI: 10.4103/abr.abr_69_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thymoquinone on Reproductive Parameter in Morphine-treated Male Mice

Abstract: Background:Thymoquinone as the main active component of Nigella sativa might have a various pharmacological effects such as antiapoptotic and antioxidant. Morphine is commonly used for the treatment of severe pain that can increase the generation of free radicals and affects the spermatogenesis. This study was designed to evaluate protective effects of thymoquinone against morphine-induced damages, sperm viability, count, motility, morphology and testis histology, and nitric oxide and testosterone hormone of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…Administration of MOR in male rats caused a significant reduction in sperm motility index and survival rate compared to control group, which confirms the results of the present study (10). In addition, the results of present study showed that GA or MOR + GA administration significantly increased the viability, motility, count and normal morphology of sperm cells compared to the MOR control group.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Administration of MOR in male rats caused a significant reduction in sperm motility index and survival rate compared to control group, which confirms the results of the present study (10). In addition, the results of present study showed that GA or MOR + GA administration significantly increased the viability, motility, count and normal morphology of sperm cells compared to the MOR control group.…”
Section: Discussionsupporting
confidence: 91%
“…It seems that a significant relationship is found among the production of oxygen species in sperms and disruption in morphology of sperms. The increased amount of free radicals results in destruction of surrounding cells, damage to Sertoli cells, the collapse of cytoplasmic bridges in which a reduction in the number of sperms and a decrease in sperm motility are probable (10). MOR administration causes a reduction in testosterone level due to the presence of oxidative stress (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations